Status of insecticide resistance in field populations of tomato fruit borer (Helicoverpa armigera) (Lepidoptera: Noctuidae) in Punjab, India - WARGANTIWAR, RAM K; KANG, B K (The Indian Journal of Agricultural Sciences, 2018)
Laboratory bioassays were conducted during 2013-14 to observe the level of insecticide resistance against tomato fruit borer [Helicoverpa armigera (Hubner)]. Populations collected from major tomato growing districts (Amritsar, ASR; Kapurthala, KPT; Patiala, PTA) of Punjab, India. Among different populations, Amritsar populations showed least susceptibility against synthetic pyrethroids, organophosphate as well as diamide followed by Patiala and Kapurthala. In the present study, fenvalerate was observed to be the least effective and have acquired high level of resistance (480-1270 fold) in H. armigera. As per the organophosphate and diamide groups of insecticides, Amritsar, Kapurthala and Patiala populations showed more susceptibility to profenofos and flubendiamide as compared to other insecticides tested. The susceptibility level against profenofos was almost same for all the tested populations. Flubendiamide was most effective insecticides against all populations. Pearson's correlation coefficient (r) showed significant relationship among fenvalerate and profenophos, deltamethrin and profenophos, flubendiamide and profenophos which suggest that resistance to profenophos, deltamethrin and flubendiamide might be due to possible cross-resistance mechanisms. However, although there was positive relationship among other insecticides, but none showed their statistical significance on log LC50 values of tested insecticides on field population of H. armigera. A strong positive correlation between monooxygenase activity and pyrethroid resistance indicated that the elevated cytochrome P450 monooxygenase activity is associated with pyrethroid resistance indifferent strains of H. armigera.